Bigfoot does not like birthday parties - Ode, Eric (Little Bigfoot, an imprint of Sasquatch Books, 2015)
"In the town of Mossy Pockets, the residents throw a birthday party for reluctant Bigfoot. The party excitement builds until it all comes to a pie-smashing disaster. But in the end, Bigfoot loves it--because even though Bigfoot does not like birthday parties, Bigfoot loves a birthday mess!"--